Analysis of differentially expressed circular RNAs in endothelial cells under impinging flow. (June 2020) - Hao, Zheng; Li, Yiyun; Yu, Nianzu; Zhao, Yeyu; Hu, Si; Liu, Zheng; Li, Meihua
Abstract: Background: Circular RNAs (circRNAs) are a special type of non-coding RNA. To elucidate the relationship between hemodynamics and the function of circRNAs in endothelial cells (ECs), a modified T chamber system was designed and produced for the present experiment. This T chamber system can be used to simulate the hemodynamic environment at the bifurcation of the arteries. Methods: Normal ECs cultured on glass slides were placed in the T chamber, the cell layer was impacted at a flow rate of 500 mL/min, and high-throughput microarrays were used to analyze the expression profiles of circRNAs in ECs. The differential expressions of circRNAs in the ECs treated with impinging flow were compared to those in ECs in conventional culture conditions. The characteristics of the differentially expressed circRNAs were analyzed with bioinformatics and quantitative reverse transcription polymerase chain reaction analyses were conducted to verify results. Results: Compared to normal samples, there were changes in the expressions of many circRNAs. A total of 974 circRNAs were differentially expressed, and of these, 378 were upregulated and 596 were downregulated (fold change [FC] ≥ 2 and P < 0.05), which suggests that these circRNAs were altered under hemodynamic conditions. Conclusions: We present the differential expression profiles of circRNAs in ECs after the application of impinging flow; our results indicate that these differentially expressed circRNAs may be involved in inflammatory responses and damage in ECs. The present findings provide valuable information on cRNA profiles as well as clues for future studies that will investigate the roles that circRNAs play in ECs after inflammatory injury. Highlights: We simulated the formation of an intracranial aneurysm and designed and improved a T flow chamber system. Under the action of impinging flow, the expression of circular RNA in HUVEC is dysregulated. Bioinformatics analysis were performed on the parental genes of differentially expressed circular RNA. To explore the potential role of circular RNA in the formation of intracranial aneurysms through bioinformatics analysis.